Mother's Knowledge Level at Sukoharjo Healthy Pharmacy About Children's Diarrhea - Atur Semartini; Purwati, Lilik; Eka Wisnu Kusuma (Journal of Scientific Research, Education, and Technology (JSRET), 2022)
Diarrhea is a disease whose morbidity and mortality rates are relatively high in the world. The world's diarrhoea cases are around 2.2 million of them have died predominantly in children under 5 years of age from cases of about 4 billion according to WHO. Mothers play an important role in taking care of children, especially when children experience diarrhea. If diarrhea occurs, the first mother will take action to treat it. The actions performed by a mother largely depend on the level of knowledge. The level of maternal knowledge about the definition of diarrhea, causes, signs and symptoms, impact, prevention and proper management plays an important role in reducing the rate of pain and death due to diarrhea in children. This research is very important to be carried out at Apotek Sehat Sukoharjo aims to find out the level of maternal knowledge at Apotek Sehat Sukoharjo about child diarrhea. The research conducted using quantitative descriptive methods, the total sample of 106 respondents. Data collection using purposive sampling technique. The instrument in this study was in the form of a questionnaire with 2 relative answers. The results of the research on the Level of Maternal Knowledge at The Sukoharjo Healthy Pharmacy about Child Diarrhea are good with a value of 78.30%.